Medial Prefrontal Cortex–Pontine Nuclei Projections Modulate Suboptimal Cue-Induced Associative Motor Learning. (11th January 2017) - Wu, Guang-Yan; Liu, Shu-Lei; Yao, Juan; Sun, Lin; Wu, Bing; Yang, Yi; Li, Xuan; Sun, Qian-Quan; Feng, Hua; Sui, Jian-Feng
Abstract: Diverse and powerful mechanisms have evolved to enable organisms to modulate learning and memory under a variety of survival conditions. Cumulative evidence has shown that the prefrontal cortex (PFC) is closely involved in many higher-order cognitive functions. However, when and how the medial PFC (mPFC) modulates associative motor learning remains largely unknown. Here, we show that delay eyeblink conditioning (DEC) with the weak conditioned stimulus (wCS) but not the strong CS (sCS) elicited a significant increase in the levels of c-Fos expression in caudal mPFC. Both optogenetic inhibition and activation of the bilateral caudal mPFC, or its axon terminals at the pontine nucleus (PN) contralateral to the training eye, significantly impaired the acquisition, recent and remote retrieval of DEC with the wCS but not the sCS. However, direct optogenetic activation of the contralateral PN had no significant effect on the acquisition, recent and remote retrieval of DEC. These results are of great importance in understanding the elusive role of the mPFC and its projection to PN in subserving the associative motor learning under suboptimal learning cue.